Virginia Woolf’s “New School of Biographies” and Eighteenth-century Life-Writing: a Sense of Kinship - Maryam Thirriard (Sillages Critiques)
Woolf was often critical of the way biographers practiced their art and the instances of her commendation of them are rare. However, in the 1920s, it became clear to her that a stark change had come over the way lives were being written. This resulted in her 1927 essay “The New Biography” in which she praises Harold Nicolson as well as Lytton Strachey for making it new. Woolf brings these life-writers together in what she calls a “new school of biographies” (“The New Biography”). At the same time, her essay provides a lengthy history of the genre and Woolf takes her readers back in time to Boswell’s The Life of Samuel Johnson, connecting him to the New Biographers and their narrative techniques. This paper explores the way in which Woolf, Lytton and Nicolson describe, through their criticism of biography, the eighteenth century as being a golden age for biography, in accordance with the principles Woolf set in her essay “The New Biography”. The assessment of the relation these New Biographers’ maintained with the previous centuries shows that their hostility towards the Victorian age was not an indiscriminate loathing of the past. On the contrary, as can be perceived in Woolf’s essay on the revolution in biography, she and her fellow modernist biographers intend to draw a bridge between the art of biography of their time and that of the eighteenth century. This paper examines the dynamic of instability the New Biographers created between old and new forms in modernist life-writing.